2020
DOI: 10.1103/physreva.102.012201
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-classical dynamical distance and quantumness of quantum walks

Abstract: We introduce a fidelity-based measure, D QC (t), to quantify the differences in the dynamics of classical versus quantum walks over a graph. We provide universal, graph-independent, analytic expressions of this quantumclassical dynamical distance, showing that at short times D QC (t) is proportional to the coherence of the walker, i.e., a genuine quantum feature, whereas at long times it depends only on the size of the graph. At intermediate times, D QC (t) does depend on the graph topology through its algebra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The Laplacian acts as a node to node transition matrix. The Hamiltonian of the CTQW can be written as [ 68 , 75 , 77 , 82 , 84 , 85 , 96 , 97 , 98 , 99 , 100 , 101 ].…”
Section: Modeling the Qd System As A Spatial Network: The Proposedmentioning
confidence: 99%
See 1 more Smart Citation
“…The Laplacian acts as a node to node transition matrix. The Hamiltonian of the CTQW can be written as [ 68 , 75 , 77 , 82 , 84 , 85 , 96 , 97 , 98 , 99 , 100 , 101 ].…”
Section: Modeling the Qd System As A Spatial Network: The Proposedmentioning
confidence: 99%
“…We characterize the network’s transport efficiency by using the average return probability , defined as [ 85 ] where the operator , stated in Equation ( 12 ), is the unitary time evolution operator governing the evolution of the probability amplitudes. Please note that, as shown in a number of papers [ 68 , 75 , 77 , 82 , 84 , 85 , 96 , 97 , 98 , 99 , 100 , 101 ], the Hamiltonian of the network is the Laplacian matrix (also called Connectivity matrix in some contexts).…”
Section: Experimental Work: Simulationsmentioning
confidence: 99%
“…In our approach, the matrix elements take different values as they depend on the involved overlap integrals and Boltzmann factors ( ) and, as shown throughout the paper, they play a natural role in the probability for an electron to hop from one node to another. The Laplacian acts as a node-to-node transition matrix so that the Hamiltonian of the CTQW can be written as [ 50 , 58 , 60 , 65 , 67 , 68 , 93 , 94 , 95 , 96 , 97 , 98 ].…”
Section: Approaching the Qd System By A Network With Spatial And Physical-based Constraintsmentioning
confidence: 99%
“…Regarding this, we can characterize the network’s transport efficiency by using the average return probability (ARP), , defined as [ 68 ] where the operator , presented in Equation ( 50 ), is the unitary time evolution operator governing the evolution of the probability amplitudes. Please note that, as shown in a number of papers [ 50 , 58 , 60 , 65 , 67 , 68 , 93 , 94 , 95 , 96 , 97 , 98 ], the Hamiltonian of the network is the Laplacian matrix (also called the connectivity matrix in some contexts). We have also shown that , the matrix form of the TB Hamiltonian in the second quantization—Equation ( 44 )—with , meaning that the unitary time evolution operator in quantum mechanics is equivalent to …”
Section: Simulation Workmentioning
confidence: 99%
“…Quantum random walks on graphs exhibit, in general, a different behaviour than their classical counterparts [2][3][4][5]. A continuous-time quantum walk (CTQW), for example, spreads on the line quadratically faster than its classical analogue, whereas there are particular graphs, such as the glued-tree graph [6] where such "speed-up" is even exponential.…”
Section: Introductionmentioning
confidence: 99%